Social participation and acceptance of disability in young and middle-aged breast cancer patients after surgery: A 6-month follow-up study - Mengyao Zhu; Yiheng Zhang; Haiyan He; Lili Chen; Juanjuan Chen; Meifen Zhang (Elsevier, 2023)
Objective: To describe the social participation and acceptance of disability (AOD) in young and middle-aged patients with breast cancer after surgery and their dynamic trajectories and to explore the critical factors associated with social participation. Methods: 212 young and middle-aged patients with breast cancer after surgery were recruited for a 6-month follow-up study, and 158 of whom completed four surveys. Participants were asked to complete questionnaires including a general information questionnaire, Social Dysfunction Screening Scale, and Adaptation of Disability Scale Revised at baseline, and at 1, 3, and 6 months. T-test and chi-square test were used to analyze the difference in baseline data. Linear generalized estimating equations were used to analyze the dynamic trend and influencing factors. The Cochran-Armitage trend test was used to analyze the trend of the incidence of social function defects. Results: The status of social participation in patients after breast cancer surgery was poor, and 77.9%, 59.3%, 45.9%, and 29.1% had social function defects, respectively. The AOD was at a moderate level. Both social participation and AOD showed a trend of dynamic improvement. Age (P ​= ​0.044), residence (P ​= ​0.007), surgery type (P ​= ​0.043), postoperative chemotherapy (P ​= ​0.003), and AOD (P < 0.001) were the key factors associated with social participation. Conclusions: Medical staff should focus on elderly patients, who lived outside the provincial capital city, received total mastectomy, or modified radical mastectomy and postoperative chemotherapy. AOD might be an important potential avenue for improving the social participation level of young and middle-aged patients with breast cancer after surgery.